2011
DOI: 10.1002/pat.1864
|View full text |Cite
|
Sign up to set email alerts
|

High strength electrospun fibers

Abstract: Electrospinning provides a simple method to process solutions or melts, mainly of polymers, into continuous ultrathin fibers. However, the mechanical properties of electrospun fibers are low due to non‐optimized macromolecular orientation in the fibers. The methods of CNT reinforcement and heat‐induced orientation of rigid macromolecular chains are used to prepare high strength electrospun fibers. This paper presents an overview of these high strength electrospun fibers, with focus on the progress achieved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…And later a new carbon layer was formed because of the IFR MPP, then the third and the fourth HRR peak appeared. [36] Compared with neat TPU, the ignition time (IT) of TPU composites was earlier; it may be because of the expansion of samples before ignition in the cone, which made the distance wileyonlinelibrary.com/journal/pat between the cone and the surface of samples smaller, and the thermal radiation flux becomes stronger, promoting the decomposition of polymers. It can also be seen from Fig.…”
Section: Heat Release Ratementioning
confidence: 99%
“…And later a new carbon layer was formed because of the IFR MPP, then the third and the fourth HRR peak appeared. [36] Compared with neat TPU, the ignition time (IT) of TPU composites was earlier; it may be because of the expansion of samples before ignition in the cone, which made the distance wileyonlinelibrary.com/journal/pat between the cone and the surface of samples smaller, and the thermal radiation flux becomes stronger, promoting the decomposition of polymers. It can also be seen from Fig.…”
Section: Heat Release Ratementioning
confidence: 99%
“…The BP‐PI is a homo‐PI with rigid‐rod‐like chemical structures, and its macromolecular backbone consists of benzene rings and imide structures. It has been reported that electrospun BP‐PI nanofiber belt (prepared at the thermal imidization temperature of 430 °C) had the tensile stress and modulus as high as 663.7 MPa and 15.3 GPa, respectively . Note that the imidization temperature has a significant influence on mechanical properties; at the low imidization temperature of 300 °C, the BP‐PI nanofiber belt showed the tensile stress, modulus, and strain of 367.3 MPa, 9.1 GPa, and 4.68%, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…First, the good compatibility and interfacial adhesion between BP‐PI nanofiber filler and HO‐PI matrix would make the resulting nanocomposite films to possess high tensile stress and modulus. Second, the BP‐PI nanofibers with rigid macromolecular backbone would become stronger after the hot‐pressing treatment at higher temperature of 350 °C (which was higher than the thermal imidization temperature of 300 °C), because of the thermal‐induced crystallization and molecular orientation . This was also the reason why the stress of neat BP‐PI nanofiber belt was increased from 300.5 to 388.0 MPa, and the modulus was increased from 7.79 to 8.27 GPa, after the hot‐pressing treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Polyimide (PI) represents a class of high performance heteroaromatic polymers known as their high thermal resistance, good mechanical and dielectric properties, and excellent environmental stability [14][15][16]. Thus, PI materials, especially wholly aromatic ones have been considered to be one of the best candidates as high performance PUFs [17][18][19]. Various wholly aromatic PI fibers, including poly(pyromellitic anhydrideoxydianiline) (PMDA-ODA) and poly(biphenyl dianhydride-p-phenylenediamine) (BPDA-PDA) PUFs have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%